2020
DOI: 10.7717/peerj.10035
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression profiles of candidate chemosensory receptors in Histia rhodope (Lepidoptera: Zygaenidae)

Abstract: Insect olfaction and vision play important roles in survival and reproduction. Diurnal butterflies mainly rely on visual cues whereas nocturnal moths rely on olfactory signals to locate external resources. Histia rhodope Cramer (Lepidoptera: Zygaenidae) is an important pest of the landscape tree Bischofia polycarpa in China and other Southeast Asian regions. As a diurnal moth, H. rhodope represents a suitable model for studying the evolutionary shift from olfactory to visual communication. However, only a few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 87 publications
(124 reference statements)
1
1
0
Order By: Relevance
“…By comparing and analyzing the amino acid sequences of ORs, it has been found that the homology of ORs among different insects is very low, and ORs among the same kind of insects are also dispersed, which may be related to ORs’ participation in recognition of odorants [ 43 ]. This study supports the evidence from previous observations that ORCO has high homology among different species, and an insect usually contains only one ORCO [ 44 ]. Compared with ORs, IRs only have three transmembrane domains.…”
Section: Discussionsupporting
confidence: 92%
“…By comparing and analyzing the amino acid sequences of ORs, it has been found that the homology of ORs among different insects is very low, and ORs among the same kind of insects are also dispersed, which may be related to ORs’ participation in recognition of odorants [ 43 ]. This study supports the evidence from previous observations that ORCO has high homology among different species, and an insect usually contains only one ORCO [ 44 ]. Compared with ORs, IRs only have three transmembrane domains.…”
Section: Discussionsupporting
confidence: 92%
“…IRs are conserved across protostome species and bioinformatic analyses of IR genes have been performed in many species (Benton et al, 2009 ; Croset et al, 2010 ; Bengtsson et al, 2012 ; Glaser et al, 2013 ; Poivet et al, 2013 ; Rytz et al, 2013 ; Cao et al, 2014 ; Groh-Lunow et al, 2014 ; Liu et al, 2014 , 2017 , 2018 ; Missbach et al, 2014 ; Ahmed et al, 2016 ; Dippel et al, 2016 ; Macharia et al, 2016 ; van Schooten et al, 2016 ; Cicconardi et al, 2017 ; Latorre-Estivalis et al, 2017 ; Yang et al, 2017 , 2020 ; Zbinden et al, 2017 ; Harrison et al, 2018 ; Kozma et al, 2018 ; Matthews et al, 2018 ; Robertson et al, 2018 , 2019 ; Rojas et al, 2018 ; Andersson et al, 2019 ; Lei et al, 2019 ; Li et al, 2019 ; Ma et al, 2019 ; Xu et al, 2019 ; Balart-García et al, 2020 ; Sun et al, 2020 ; Wu et al, 2020 ; Yin et al, 2020 ). However, the functional studies of IRs in non-model organisms are largely lacking.…”
Section: Discussionmentioning
confidence: 99%